2008
DOI: 10.1167/iovs.07-1121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bcl-XL-Interacting Protein FKBP8 and Its Splice Variant in Human RPE Cells

Abstract: FKBP8 and its novel splice variant are Bcl-XL-interacting proteins and regulate the apoptotic signaling pathways in the RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The PRL-1 binding proteins identified by Lee et al included TPD54, NDUFB8 (NADH:ubiquinone oxidoreductase subunit B8), and FKBP38. NDUFB8 and FKBP38 are known to have mitochondrial localizations [43]. Now, we have shown that TPD54 also has a mitochondrial distribution and interacts with PDH E1α in breast cancer cells, indicating its potentially important role in the metabolic regulation in cancer.…”
Section: Discussionmentioning
confidence: 86%
“…The PRL-1 binding proteins identified by Lee et al included TPD54, NDUFB8 (NADH:ubiquinone oxidoreductase subunit B8), and FKBP38. NDUFB8 and FKBP38 are known to have mitochondrial localizations [43]. Now, we have shown that TPD54 also has a mitochondrial distribution and interacts with PDH E1α in breast cancer cells, indicating its potentially important role in the metabolic regulation in cancer.…”
Section: Discussionmentioning
confidence: 86%
“…One milligram of the cell lysate was incubated overnight with 20 μ L anti–Hsc70 antibody (200 μ g/mL; Santa Cruz Biotechnology, Santa Cruz, CA) or 15 μ L anti–HNE antibody (200 μ g/mL; R&D Systems, Minneapolis, MN). Protein G-agarose beads (Upstate, Lake Placid, NY) were used to pull down the antibody and the bound proteins 26. After stringent washes, the immunoprecipitates were boiled in 2× Laemmli sample buffer (Bio-Rad), separated by 12% SDS-polyacrylamide gel, and subjected to Western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…24 Detection of senescence-associate heterochromatin foci (SAHF) was performed as described in the literature. 25,26 Briefly cells were fixed with 4% formaldehyde and then permeabilized with 0.2% Triton X-100.…”
Section: Indirect Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%